2019
DOI: 10.1021/acsomega.9b00569
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding of the Burial Environment from the Chemical Biography of Archeological Copper-Based Artifacts

Abstract: The long-term interaction between Cu-based alloys and environmental species gives rise to the formation of different and sometimes unusual compounds (i.e., the patina) with distinctive chemical and structural features as a function of the peculiar characteristics of the context. In this paper, we describe some representative case studies concerning degraded bronze Roman valuable or common use objects, and we show that an attentive study at a microscale level, as for forensic analysis, allows one to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…28 Metabolic activity of sulfate-reducing bacteria (SRBs) in the soil, producing copper and copper-iron sulfides in anaerobic conditions, could be another source of the element. 29,30 A noteworthy feature is the relatively high concentration of phosphorus in some cases. The element is sometimes present in iron-rich silicates mentioned above, but contact with decomposed organic matter like peat is also a possible source.…”
Section: Elemental Analysismentioning
confidence: 99%
“…28 Metabolic activity of sulfate-reducing bacteria (SRBs) in the soil, producing copper and copper-iron sulfides in anaerobic conditions, could be another source of the element. 29,30 A noteworthy feature is the relatively high concentration of phosphorus in some cases. The element is sometimes present in iron-rich silicates mentioned above, but contact with decomposed organic matter like peat is also a possible source.…”
Section: Elemental Analysismentioning
confidence: 99%
“…With technological and scientific progress, there is a strong expectation for greener and safer procedures for the removal of corrosion products such as from ancient metal artifacts. Copper was one of the first metals to be used by humans; copper-based artifacts have been the most frequently found objects in archaeological sites throughout history [ 1 ] and are generally found with a layer of naturally developed patina on their surfaces. Without any specific treatment, corrosion continuously spreads over the objects and destroys their fine structures.…”
Section: Introductionmentioning
confidence: 99%
“…There are several interesting cases studio about the possibility to reconstruct the history of a bronze artifact trough the analysis of patinas 14 i.e. Ingo et al identified by a turquoise crust the interaction of a roman coin with phosphorous released by animal bones discarded into the ancient sewer 15 or correlated the accumulation of metal on the Dancing Satyr with the marine context 16 .…”
Section: Introductionmentioning
confidence: 99%